Electroporation-Based Treatments in Small Animal Veterinary Oral and Maxillofacial Oncology - Nemec, Ana; Milevoj, Nina; Lampreht Tratar, Urša; Serša, Gregor; Čemažar, Maja; Tozon, Nataša (Frontiers in Veterinary Science, 2020)
Electroporation is a method of inducing an increase in permeability of the cell membrane through the application of an electric field and can be used as a delivery method for introducing molecules of interest (e.g., chemotherapeutics or plasmid DNA) into cells. Electroporation-based treatments (i.e., electrochemotherapy, gene electrotransfer and their combinations) have been shown to be safe and effective in veterinary oncology, but they are currently mostly recommended for the treatment of those solid tumors for which clients have declined surgery and/or radiotherapy. Published data show that electroporation-based treatments are also safe, simple, fast and cost-effective treatment alternatives for selected oral and maxillofacial tumors, especially small squamous cell carcinoma and malignant melanoma tumors not involving the bone in dogs. In these patients, a good local response to treatment is expected to result in increased survival time with good quality of life. Despite emerging evidence of the clinical efficacy of electroporation-based treatments for oral and maxillofacial tumors, further investigation is needed to optimize treatment protocols, improve clinical data reporting and better understand the mechanisms of patients’ response to the treatment.